Determinan Potensi Risiko Stunting: Sistematis Literatur Review - Wiyono, Sugeng; Sumantri, Arif (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2025)
Stunting is a significant health issue affecting the world today, particularly in developing countries. The Southeast Asian region accounts for more than a quarter of all stunted children worldwide. In addition to impacting child development, mortality, and morbidity will also affect the economy and productivity of countries in the future. This scoping review aims to systematically map the research conducted in this area and identify existing knowledge gaps related to risk factors for stunting. The scoping review was conducted using three PubMed databases, the keywords used were